Epistemic agency in student teachers’ engagement with research skills - Mirva Heikkilä; Hege Hermansen; Tuike Iiskala; Mirjamaija Mikkilä-Erdmann; Anu Warinowski (Routledge, Taylor & Francis Group, 2022)
In today’s knowledge intensive and post-factual world, student teachers’ relationship towards knowledge is a vital element in learning to teach. Student teachers must have a sense of epistemic agency to see themselves as productive participants in knowledge-laden activities. However, little attention has been paid to the role of agency in the interconnections between research and teaching in higher education. This study aims to identify how epistemic agency is manifested in student teachers’ expressions when they are provided with tools for knowledge production (educational research skills). Epistemic agency was examined as a narrative practice in student teachers’ texts (N = 73), and a data-driven analysis was conducted. The results explore the four dimensions of professional practice towards which the students directed their epistemic agency: ‘the self’, ‘the class’, ‘the research literature’, and ‘the everyday life’. The study makes visible the variety of how engagement with research skills can promote epistemic agency.